Excess Molar Volumes and Viscosity Studies of Binary Mixtures of o-Cresol and Nonanol at Different Temperatures - Narendra, K.; Tulasi Koteswari Bai, B.; Babu Rao, K.; Srinivas, S.S.J.; Sarath Babu, M. (Asian Journal of Chemistry, 2012)
Ultrasonic velocity, density and viscosity have been measured for the binary mixtures of o-cresol and nonanol at 303.15, 308.15, 313.15 and 318.15 K and at atmospheric pressure. The experimental data obtained has been used to calculate the acoustical parameters namely adiabatic compressibility (b), free length (Lf), free volume (Vf), internal pressure (p), acoustic impedance (Z) and molar volume (Vm). The excess values like excess molar volume and excess viscosity were evaluated and the results were fitted into Redlich-Kister equation. The results were also used to explain the molecular interaction between the components of these mixtures.